Prácticas De Enseñanza Y Aprendizaje Tradicional Del Tiple Colombiano En Tres Maestros Artistas Del Territorio Sonoro De La Canta y El Torbellino. - Rodríguez Ramírez, Edwin Johanni (Universidad Antonio Nariño, 2023)
This research shows the particularities of the teaching and learning processes of the tiple (Colombian national instrument) in three master artists from the sound territory of canta y el torbellino (TSCT) located in the departments of Boyacá and Cundinamarca, a geographical space where investigation takes place. The proper description of the findings is made based on the assumption that the transmission of traditional knowledge presents significant and particular differences, which differ according to the socio-cultural context, making, in turn, a recognition of a work that keeps the knowledge current. and the memory of a region, under the concept of cultural identity.